Predicting corporate bankruptcy: A cross-sectoral empirical study : the case of Greece - Nikolaos Arnis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2018)
Purpose: Beginning from the assumption that accrual accounting is useful in ensuring the high performance of management systems, this article investigates explanatory factors concerning the level of accrual accounting adoption in municipalities on the Indonesia island of Java. Design/methodology/approach: Data collection in this study was based on a structured questionnaire sent to the Head of Accounting Sections of 119 Javanese municipalities. The instrument for content and construct validity and reliability was tested. Then, the hypotheses were tested using Structure Equation Modelling (SEM) by SmartPLS. Findings: The results indicate that the variables of top management support, adequate training programs, and the quality of information technology has a significant effect on the level of accrual accounting adoption and key are factors influencing the level of accrual accounting adoption. They also indicate that organizational culture is an important moderating influence between these variables and the level of accrual accounting adoption. Research limitations/implications: One of the limitations of this study is that data collection using a survey method through a questionnaire likely does not capture the wider knowledge of respondents; in addition, the questionnaires were distributed only to Javanese municipalities. The findings of this study and the limitations inherent in it can lead to some further research opportunities. For example, further research can examine neglected variables such as the size of the organization and its social capital and also the importance of organizational variables such as local political support and support from external auditing processes. Originality/value: To the best of the researcher's knowledge, no study of Indonesian municipalities has tested the impact of factor such as top management support, and organizational culture as a moderating effect on the level of accrual accounting adoption.
Keywords: C38; C53; G33; M 41; 330; Bankruptcy; Corporate Bankruptcy; Sectoral Forecasting Models; Financial Ratios